Critique of Archaeological Reason : Structural, Digital and Philosophical Aspects of the Excavated Record - Buccellati, Giorgio
"The inquiry into the nature of archaeology and its theoretical presuppositions leads to unexpected results. The question about its nature is a question about distinctiveness: what is unique about the discipline that sets it apart from the others? The question about theoretical presuppositions relates to the conditions that make this distinctiveness possible: what is the frame of reference within which such uniqueness can best be understood? Unexpected results emerge when one sees archaeological reason emerge as an independent dimension of human reason and become a mode of thought. As such, it affects the way in which we view reality, so that the theoretical presuppositions loom even larger, and require a correspondingly fuller elaboration"--